ANALISIS KEPUTUSAN NASABAH MENABUNG : PENDEKATAN KOMPONEN DAN MODEL LOGISTIK STUDI KASUS PADA BANK SYARIAH DI KOTA BATAM - Dian Lestari Siregar; Rio Rahmat Yusran (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The characteristics of the sharia banking system which operate on the basis of profit sharing principles provide an alternative banking system that is mutually beneficial to the public and banks,and highlighting aspects of fairness in transactions, ethical investment, promoting the values ​​of togetherness and brotherhood in production, and avoiding speculative activities in financial transactions. By providing a variety of products and diverse banking services with more varied financial schemes, Islamic banking becomes a credible alternative banking system and can be demanded by all classes of Indonesian people without exception, but there are still many people who are hesitant to save at Islamic banks. This is because the public lacks information about Islamic banks, and does not understand the prevailing system of Islamic banking. By analyzing the Component Approach and Logistics Model, the research aims, first to find out what factors influence the customer's decision to save in Islamic banks, second to find out how much influence these factors have on the customer's decision in choosing an Islamic bank and third to find out which factor is the most dominant factor in the customer's decision to save at an Islamic bank